Fourier transform-electron spin resonance study of spin polarization generated by triplet- and radical-pair mechanisms in a photoinduced electron transfer reaction - Plüschau, Marc; Zahl, Achim; Dinse, K.; van Willigen, H. (Journal of Chemical Physics, 1989)
Fourier transform-electron spin resonance (FT-ESR) was utilized to measure the photoinduced charge transfer in the system Zn tetraphenylporphyrin/ duroquinone with a time resolution of 10 ns. The separate observation of the intensity/time profile of different hyperfine lines in the spectrum, which was made possible by application of FT-ESR, enabled the independent determination of transient acceptor radical polarization originating from the triplet- and radical-pair mechanism. The observed temperature dependence and the absolute value of the electron transfer rate lead to the conclusion that the process is diffusion limited with no indication of an activation barrier. © 1989 American Institute of Physics.